Reflexões sobre a intensificação de adjetivos modais epistémicos por ’muito’ e ’bem’ em Português Europeu - Cantante, Inês (Revista da Associação Portuguesa de Linguística, 2021)
Our research aims to investigate the semantic differences between muito (much/very) and bem (well), as degree modifiers, when applied to modal adjectives. These adjectives, contrary to the qualificative ones, predicate over situations and not individuals. Although these intensifiers, that is, muito and bem, are in some ways similar to each other, they also have several differences, as observed by Quadros Gomes (2011). Previous work (Horn, 1989; Oliveira, 1988; 2000; 2013; Ferreira, 2013; Cantante, 2018; 2020, e.o.) has shown that modal adjectives, like qualificative adjectives, are gradable and, therefore, ordered along a scale. Taking into consideration this similarity between these two types of adjectives, and, also, the differences between muito and bem, the present work aims to explore the scalar behaviour of epistemic modal adjectives, particularly when intensified by these degree modifiers. While investigating the adjectives possível (possible), provável (probable), necessário (necessary) and certo (certain) (the latter being the only adjective located on the top of the scale), this research allowed us to find that, apart from certo, which did not accept to be modified by muito, both these adverbs act by moving the adjectives to higher points of the scale. However, it is not evident, contrary to Quadros Gomes’ claims (2011), that bem has the capacity to put these adjectives on the top of the scale, therefore closing it. It is also important to acknowledge that, although bem moves the adjectives to higher points of the scale – even higher than the movement promoted by muito – this adverb, when modifying modal adjectives, seems to contain a second component to its meaning, which involves a modal evaluation, responsible for emphasizing the degree of certainty of the speaker regarding the situation described in the utterance.